Present Status and Future Perspectives on Dioxins/Furans and Polychlorinated Biphenyls Policies in Malaysia - Nurul Izzati Azmi; Yin-Hui Leong; Mohamed Isa Abdul Majid (Annals of Environmental Science and Toxicology - Peertechz Publications, 2017)
Dioxins/furans and polychlorinated biphenyls (PCBs) are persistent organic pollutants (POPs) that are lipophilic and toxic in the environment. These contaminants are found in some soils, sediments, feed and food, especially dairy products, meat, fi sh and shellfi sh. The main pathway of human exposure to these pollutants is via food ingestion, estimated at over 95% of the total intake for non-occupationally exposed persons. They last a long time once they enter into the body due to their chemical stability and their lipophilic characteristic whereby they absorb by fat tissue and store in the body. Dioxins and furans contaminants are released through combustion, such as waste incineration, forest fi res, volcanic eruptions and some industrial processes while PCBs are man-made chemicals and has been used because of their stability and low fl ammability as insulating materials in electrical equipment. Waste management is a general acute problem around the world. As one of the developing countries, Malaysia is undergoing economic growth, industrialization and urbanization, thus the proper management of larger quantity of waste being generated is of great concern. For this issue, hazardous waste from industries especially, is becoming a topic of one cannot deny that requires immediate attention. The efforts to reduce the emission of dioxins/furans and PCBs into the environment are being initiated when Malaysia agreed in the Stockholm Convention on Persistent Organic Pollutants in 2002. The toxicity of these contaminants in food/feed, air and sludge samples is monitored routinely. However, intensive measures to prevent the formation of dioxins/furans at the source have not been widely implemented. This paper describes the policies and regulations of dioxins/furans and PCBs in Malaysia. It also addresses the health risk assessment on certain food items and some potential strategic measures are recommended and evaluated.